The future of European development finance: Institutional reforms for sustainable solutions - Benedikt Erforth; Lennart Kaplan (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Climate change, migration flows, security - growing challenges like these are calling for new responses from EU development policy. Achieving the Sustainable Development Goals (SDGs) by 2030 will in itself require additional financial resources of up to USD 2.5 trillion every year in middle- and low-income countries. Although the European Union (EU) and its Member States are already the biggest donors worldwide, the amount of public funds available is not enough to reach the SDGs. In their search for solutions, therefore, state and non-state actors are focusing squarely on linking public- and private-sector funding. Faced with ambitious climate targets and China's growing involvement in development finance, the current debate on the EU's future external financing is centred around reforming the institutional architecture. Such reforms are intended to boost green energy and employment in the partner countries and communicate a coherent European model of socioeconomic development to the outside world. While all actors agree that the EU's external financing architecture should be simpler, more visible and more efficient (European Commission, 2018), views on how this could actually be achieved vary widely. This led the Council of the EU to task a high-level Wise Persons Group with formulating various scenarios for creating an EU Development Bank. EU development financing is plagued by conflicting national and supranational interests and often sees institutional concerns prioritised over matters of content. Against this backdrop, we argue that institutional and content-related interests need to be better aligned if development financing is to be made more efficient and more sustainable. In particular, a reformed architecture for the EU's external financing has to do more to reconcile European sustainability and development goals with the needs of partners. Measuring impact against uniform standards will both help to achieve overarching objectives and convey a successful European development model. Given the importance of private capital for development finance, a reformed financial architecture should also consider the interests and rationales of the private sector. However, this will only be a winning formula if social, environmental and human rights standards do not take a back seat.
Keywords: 330